2017
DOI: 10.3390/rs9010096
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Terrain Classification Based on Multilayer Bayesian Network and Conditional Random Field

Abstract: This paper presents a hierarchical classification approach for Synthetic Aperture Radar (SAR) images. The Conditional Random Field (CRF) and Bayesian Network (BN) are employed to incorporate prior knowledge into this approach for facilitating SAR image classification.(1) A multilayer region pyramid is constructed based on multiscale oversegmentation, and then, CRF is used to model the spatial relationships among those extracted regions within each layer of the region pyramid; the boundary prior knowledge is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…For example, Ronny Hansch [8] used complex neural network to realize PolSAR data learning and classification. He [9] achieved hierarchical terrain classification based on bayesian network and conditional random field in 2017. However, there are essential differences between the imaging mechanism of optical image and SAR imagery.…”
Section: Sar Imagery Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ronny Hansch [8] used complex neural network to realize PolSAR data learning and classification. He [9] achieved hierarchical terrain classification based on bayesian network and conditional random field in 2017. However, there are essential differences between the imaging mechanism of optical image and SAR imagery.…”
Section: Sar Imagery Feature Extractionmentioning
confidence: 99%
“…On the other hand, attribute information in PolSAR imagery is quite precise and complex, manual features can not automatically adapt to data itself. Lots of work have confirmed that feature learning is superior to traditional methods for PolSAR image interpretation [9,24]. Feature learning methods complete underlying feature abstraction through network layers iteratively, so as to learn data's essential information.…”
Section: Problems and Motivationmentioning
confidence: 99%
“…should be concerned, hence an mount of region-based methods have been developed. A common way is to use the Markov random field and conditional random field to model the spatial interactions [9][10][11], or segment data into homogeneous objects [12]. In addition, some researchers also undertake to combine the neural network models with superpixel segmentation to remedy this matter [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The final result will emphasize the color that most represents the terrain type (eg, blue for water). Additionally, frequency domain [7,8], segmentation [6,9,10], bayesian network [11], and Hyperspectal Images [12] can also be used in terrain classification.Other types of sensors such as LiDAR [13][14][15][16] can complement the classification decision. Algorithms that use laser scanners proved to be qualified to accurately distinguish between water and non-water terrains [13][14][15][16].…”
mentioning
confidence: 99%
“…The final result will emphasize the color that most represents the terrain type (eg, blue for water). Additionally, frequency domain [7,8], segmentation [6,9,10], bayesian network [11], and Hyperspectal Images [12] can also be used in terrain classification.…”
mentioning
confidence: 99%